MOBILE APPLICATIONS AS A TOOL FOR ORGANISING NETWORKING - Nikolay Nikolaevich Sukhorukov (Science and Innovation Center Publishing House, 2020)
Networking – it is a relatively new concept. Nevertheless, several hundred networking-events are held annually in Russia alone. The importance of networking cannot be underestimated – it allows us to solve a wide range of tasks in personal life and business. Networking is one of the most effective and least expensive tools for expanding social capital and doing business. However, the organization and conduct of networking events is a long, laborious process but now this activity can be partially automated by using mobile applications.